Pengaruh Problem Based Learning terhadap Kemampuan Bernalar Kritis Siswa Sekolah Dasar - Huda, Moh. Khoridatul; Firdausi, Rofiqoh; Salsabila, Zulfa Qomariyah (Sekolah Tinggi Agama Islam Taruna Surabaya, 2024)
One of the ways to enhance students’ critical reasoning skills is by using the Problem-Based Learning (PBL) model. It can help students improve critical reasoning skills in mathematics. The research aims to determine the effect of PBL on the critical reasoning abilities of MI Tarbiyatul Huda students. This research employed quantitative research using an experimental approach with a quasi-experimental. This research used a Pre-test and Post-test Control Group Design. The method used to obtain data is using test. Meanwhile, the data analysis technique used was hypothesis testing analysis using SPSS Statistics ver. 2.6. Based on the results of the analysis, it is found that the F test shows that the F value = 0.466 with a probability significance level of 0.761 > 0.05. It can be concluded that H0 is rejected and H1 is accepted. It means that the hypothesis is accepted. It means that there is a significant influence of the PBL model in statistical material on the critical reasoning abilities of class VI MI Tarbiyatul Huda students.